Legal Review of Cases of Defective Goods in Online Shopping Transactions through E-Commerce Platforms - Imelda Martinelli; Karen Eklesia Gabriella Kaendo; Maulida Syahrin Najmi (Asian Journal of Social and Humanities, 2023)
This journal discusses how the legal protection review relates to losing goods or money in online transactions. In this digital era, online transactions that are increasingly popular have become part of people's daily lives, so strong legal regulations are needed to avoid scamming and other losses. This research aims to increase public awareness of conducting online transactions because we know that in online transactions, we cannot know whether the goods sold by the seller are true or not. The research method of this journal uses the Library Method by using primary and secondary study materials, such as articles, journals, and others, and a Normative Juridical approach. The conclusion of the research states that online fraud in the form of defects in ordered goods is very common, and the majority of people affected by scamming do not know what actions to take to get their rights in the transaction other than contacting the admin of the online shop or customer service from an e-commerce company